Increased Relative Abundance of Ruminoccocus Is Associated With Reduced Cardiovascular Risk in an Obese Population - Arun Prasath Lakshmanan; Sara Al Zaidan; Dhinoth Kumar Bangarusamy; Sahar Al-Shamari; Wahiba Elhag; Annalisa Terranegra (Frontiers in Nutrition, 2022)
BackgroundObesity is a complex disease with underlying genetic, environmental, psychological, physiological, medical, and epigenetic factors. Obesity can cause various disorders, including cardiovascular diseases (CVDs), that are among the most prevalent chronic conditions in Qatar. Recent studies have highlighted the significant roles of the gut microbiome in improving the pathology of various diseases, including obesity. Thus, in this study, we aimed to investigate the effects of dietary intake and gut microbial composition in modulating the risk of CVD development in obese Qatari adults.MethodsWe enrolled 46 adult subjects (18–65 years of age) who were classified based on their CVD risk scores, calculated using the Framingham formula, into a CVD no-risk group (score of <10%, n = 36) and CVD risk group (score of ≥10%, n = 10). For each study subject, we measured the gut microbial composition with a 16s rDNA sequencing method that targeted the v3-v4 region using Illumina Miseq, and their nutritional status was recorded based on 24-h dietary recall. Dietary intake, bacterial taxa summary, diversity index, microbial markers, pathway analysis, and network correlation were determined for the study subjects.ResultsThe CVD risk group showed a lower intake of vitamin D, reduced relative abundance of genera Ruminococcus and Bifidobacterium, no change in bacterial diversity, and higher levels of taurine, hypotaurine, and lipoic acid metabolism than the CVD no-risk group. Besides, the relative abundance of genus Ruminococcus was positively correlated with the intake of protein, monounsaturated fat, vitamin A, and vitamin D.ConclusionTaken together, our results suggest that the genus Ruminococcus could be used as a microbial marker, and its reduced relative abundance could mediate the risk of CVDs in the Obese Qatari population.